2012
DOI: 10.1016/j.jappgeo.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Focused time-lapse inversion of radio and audio magnetotelluric data

Abstract: Geoelectrical techniques are widely used to monitor groundwater processes, while surprisingly few studies have considered audio (AMT) and radio (RMT) magnetotellurics for such purposes. In this numerical investigation, we analyze to what extent inversion results based on AMT and RMT monitoring data can be improved by (1) time-lapse difference inversion; (2) incorporation of statistical information about the expected model update (i.e., the model regularization is based on a geostatistical model); (3) using alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…In consequence, this parameter only acts as a multiplication constant of C Δm in the inversion process and its effect is overcome by the optimization made on the regularization parameter λ (equation 3). This is also observed by Hermans et al (2012) andRosas Carbajal et al (2012) and will be illustrated for the second synthetic case. We invert for model parameter changes that can explain the variations observed in the data.…”
Section: Difference Inversion Schemesupporting
confidence: 71%
See 1 more Smart Citation
“…In consequence, this parameter only acts as a multiplication constant of C Δm in the inversion process and its effect is overcome by the optimization made on the regularization parameter λ (equation 3). This is also observed by Hermans et al (2012) andRosas Carbajal et al (2012) and will be illustrated for the second synthetic case. We invert for model parameter changes that can explain the variations observed in the data.…”
Section: Difference Inversion Schemesupporting
confidence: 71%
“…In the present application, we are instead interested in the ability of the covariance matrix to regulate the correlation length of the sought model changes (Hermans et al, 2012). We thus accept using the concept in situations, in which theoretical statistical assumptions are not strictly verified (Day-Lewis et al, 2002;Doetsch et al, 2010;Rosas Carbajal et al, 2012).…”
Section: Difference Inversion Schemementioning
confidence: 99%
“…Standard MT modelling tools such as inversion can also be adapted, for example Rees et al (2016) use cascading two-dimensional (2D) inversions to model a coal-seam gas depressurisation, where the results from the preinjection inversion are used as a prior-model for the postinjection. An improvement on cascaded inversion has been implemented by Rosas-Carbajal et al (2012), where differenced 2D MT inversions have achieved high accuracy by subtracting the prior-model response from all data and reducing the data error. High-accuracy simultaneous time-lapse 1D MT inversions have also been approximated using 2D MT codes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Various geophysical techniques have been applied in time-lapse studies that aim at inferring temporal changes in the near subsurface (e.g. LaBrecque & Yang 2001;Day-Lewis et al 2002;Ajo-Franklin et al 2007;Miller et al 2008;Doetsch et al 2010;Rosas Carbajal et al 2012). Tailored inverse formulations that reduce noise and model parametrizations that focus on temporal changes make time-lapse inversions more suitable than simple differencing of models obtained from separate inversions.…”
mentioning
confidence: 99%
“…A similar strategy was applied by Ajo-Franklin et al (2007) to better resolve subsurface variations related to CO 2 injection with crosshole seismics, and by Doetsch et al (2010) combined with joint inversion of crosshole ERT and ground-penetrating radar (GPR). More recently, Rosas Carbajal et al (2012) applied this type of inversion approach to time-lapse electromagnetic (EM) data, specifically radio magnetotelluric (RMT) and audio magnetotelluric (AMT). Inspired by the work of Falgàs et al (2009), who monitored saltwater intrusion in a coastal aquifer, Rosas Carbajal et al (2012) demonstrated significant improvements in the resulting models by incorporating information about the expected temporal changes in the subsurface and by removing systematic errors.…”
mentioning
confidence: 99%